A systematic approach to chronic heart failure care: a consensus statement. Issue 3 (4th August 2014) - Page, Karen; Marwick, Thomas H; Lee, Rebecca; Grenfell, Robert; Abhayaratna, Walter P; Aggarwal, Anu; Briffa, Tom G; Cameron, Jan; Davidson, Patricia M; Driscoll, Andrea; Garton‐Smith, Jacquie; Gascard, Debra J; et al.
Summary: The National Heart Foundation of Australia assembled an expert panel to provide guidance on policy and system changes to improve the quality of care for people with chronic heart failure (CHF). The recommendations have the potential to reduce emergency presentations, hospitalisations and premature death among patients with CHF. Best‐practice management of CHF involves evidence‐based, multidisciplinary, patient‐centred care, which leads to better health outcomes. A CHF care model is required to achieve this. Although CHF management programs exist, ensuring access for everyone remains a challenge. This is particularly so for Aboriginal and Torres Strait Islander peoples, those from non‐metropolitan areas and lower socioeconomic backgrounds, and culturally and linguistically diverse populations. Lack of data and inadequate identification of people with CHF prevents efficient patient monitoring, limiting information to improve or optimise care. This leads to ineffectiveness in measuring outcomes and evaluating the CHF care provided. Expanding current cardiac registries to include patients with CHF and developing mechanisms to promote data linkage across care transitions are essential. As the prevalence of CHF rises, the demand for multidisciplinary workforce support will increase. Workforce planning should provide access to services outside of large cities, one of the main challenges it is currently facing. To enhance community‐based management of CHF, general practitioners should be empowered to lead care. Incentive arrangements should favour provision of care for Aboriginal and Torres Strait Islander peoples, those from lower socioeconomic backgrounds and rural areas, and culturally and linguistically diverse populations. Ongoing research is vital to improving systems of care for people with CHF. Future research activity needs to ensure the translation of valuable knowledge and high‐quality evidence into practice.